A novel predictor–corrector explicit integration scheme for structural dynamics. (December 2021) - Liu, Wei; Guo, Wenhua
Abstract: A novel predictor–corrector explicit scheme is presented to solve structural dynamic problems. It is a three sub-steps method, in which the previous two sub-steps are set as predictors and the last sub-step is regarded as correctors. The explicit scheme is third-order accuracy and can achieve forth-order accuracy in the absent of physical damping. The stability limit of the proposed scheme is much larger than the existing methods. Also, the numerical dissipation and dispersion of the explicit scheme can be controlled through the different algorithm parameters. The explicit scheme not only possesses adequate numerical dissipation and dispersion in high-frequency responses, but also gets small numerical errors in the whole frequency domain for dynamic system. These performances of the proposed explicit scheme are further highlighted in comparison with other typical explicit schemes.